2015
DOI: 10.1186/s40199-015-0093-x
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic effect of the aqueous extract of Cynodon dactylon on human umbilical vein endothelial cells and granulation tissue in rat

Abstract: BackgroundCynodon dactylon, a valuable medicinal plant, is widely used in Iranian folk medicine for the treatment of various cardiovascular diseases such as heart failure and atherosclerosis. Moreover, its anti-diabetic, anti-cancer and anti-microbial properties have been also reported. Concerning the critical role of angiogenesis in the incidence and progression of tumors and also its protective role in cardiovascular diseases, we investigated the effects of the aqueous extract prepared from the rhizomes of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 40 publications
(54 reference statements)
1
30
0
Order By: Relevance
“…The widely prescribed, AMPK-activating antidiabetic drug metformin has been shown to inhibit angiogenesis in vitro and in vivo (55) and currently is being evaluated in several clinical trials for various types of cancer (56). However, the concentrations of metformin required to activate AMPK in HUVEC are at least 1,000 times higher than those required of itraconazole (in the range of low millimoles) (55), suggesting that itraconazole might be significantly more effective than metformin at inhibiting angiogenesis in patients. Another drug in trials for cancer, the natural product curcumin, also has been shown to activate AMPK and inhibit mTOR (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…The widely prescribed, AMPK-activating antidiabetic drug metformin has been shown to inhibit angiogenesis in vitro and in vivo (55) and currently is being evaluated in several clinical trials for various types of cancer (56). However, the concentrations of metformin required to activate AMPK in HUVEC are at least 1,000 times higher than those required of itraconazole (in the range of low millimoles) (55), suggesting that itraconazole might be significantly more effective than metformin at inhibiting angiogenesis in patients. Another drug in trials for cancer, the natural product curcumin, also has been shown to activate AMPK and inhibit mTOR (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…Metformin (orally, 50 mg/kg) significantly (p \ 0.01) decreased vascularization in granulomatous tissue by 34 % in rats (Soraya et al 2012). Metformin at levels between 0.5 and 3 mM significantly (p \ 0.001) reduced VEGF mRNA expression and endothelial cell migration (Soraya et al 2012).…”
Section: Ampk As a Target To Control Cancer Growth And Treatment Sensmentioning
confidence: 97%
“…Metformin activities were studied on migration of human umbilical vein endothelial cells, on VEGF levels and on angiogenesis in the rat air pouch model (Soraya et al 2012). Metformin (orally, 50 mg/kg) significantly (p \ 0.01) decreased vascularization in granulomatous tissue by 34 % in rats (Soraya et al 2012).…”
Section: Ampk As a Target To Control Cancer Growth And Treatment Sensmentioning
confidence: 99%
“…Moreover, the extract increased the expression of total VEGF in HUVECs at a concentration of (100 μl/ml). Accordingly, the aqueous extract of Cynodon dactylon promotes angiogenesis probably through stimulating VEGF expression [105]. The ethanol extract of aerial parts of Cynodon dactylon significant reduced the number of writhes and stretches induced in mice by 1.2% acetic acid solution.…”
Section: Antiinflammatory Antipyretic and Analgesic Effectsmentioning
confidence: 98%